A descriptive study on awareness about oral health among pediatric practitioners in Kanchipuram district - S Rajalingam; V Leela Rani (Wolters Kluwer Medknow Publications, 2016)
Background: Pediatricians and other health-care providers could play an invaluable role in ensuring the maintenance of optimal preventive as well as curative dental health in children. This study was aimed at assessing the pediatrician's perspective on basic oral health care in children in Kanchipuram district. Materials and Methods: A questionnaire survey was carried out among Pediatricians which covered various aspects of knowledge, attitude, and role of pediatricians in preventive dental care. The collected data were tabulated, and percent frequency distributions for responses to every question were assessed. Results: None of the participants reported that pediatricians are responsible for infant oral health presumes that pediatricians are not examining the oral cavity as a part of routine. All of the pediatricians gave nutritional counseling to the parents but only 7% of them of caries. All the pediatricians liked the concept of an association between lack of knowledge among pediatricians and pediatric dentist and establishment of a dental home along with a medical home. Conclusion: From the present study, we conclude that there is a lack of awareness about prevention of dental caries among pediatricians in Kanchipuram district. To overcome this, advocating dentists as part of well-child care and establishing dental home along with medical home. Publishing pediatric journals concerning about the oral health to improve the knowledge is also essential in promoting good oral health hygiene.